Answer:
They both have the same range
Step-by-step explanation:
375-175=200
400-200=200
(a^4 + 4b^4) ÷ (a^2 - 2ab + 2b^2)
= [(a^2 - 2ab + 2b^2) (a^2 + 2ab + 2b^2)] / (a^2 - 2ab + 2b^2)
= a^2+2ab+2b^2 =The answer
(a + b)^2 = a^2 + 2ab + b^2 => square of sums
(a - b)^2 = a^2 - 2ab + b^2 => square of deference
and of course one of most important ones:
a^2 - b^2 = (a - b)(a + b) => difference of squares
Best Answer: (a^4 + 4b^4) ÷ (a^2 - 2ab + 2b^2)
= [(a^2 - 2ab + 2b^2) (a^2 + 2ab + 2b^2)] / (a^2 - 2ab + 2b^2)
= a^2 + 2ab + 2b^2
a^4 + 4b^4 => i.e. 4a^2b^2 ,
a^4 + 4a^2b^2 + 4b^4 => a^2 + 2ab + b^2 = (a + b)^2, if : a = a^2 , b = 2b^2:
(a^2 + 2b^2)^2 = a^4 + 4a^2b^2 + 4b^4 => We can't add or subtract the value to the expression.
a^4 + 4a^2b^2 + 4b^4 - 4a^2b^2 =>
(a^2 + 2b^2)^2 - 4a^2b^2 =>
(a^2 + 2b^2 - 2ab)(a^2 + 2b^2 + 2ab) =>
(a^2 - 2ab + 2b^2) (a^2 + 2ab + 2b^2)
Greetings!
Answer:
680,000
Step-by-step explanation:
Population before growing rate: 400,000
Growing rate: 7%
Duration: 10 years
___
First, you will have to calculate how much does the population increase each year with the said rate, so you will have to multiply the rate by the population to determine that amount.
400,000 x 7/100 = 28,000
So the population increases by 28,000 each year, now you will have to multiply that amount by the amount of years to determine how much the amount of increase.
28,000 x 10 = 280,000
This means that the population has increased by 280,000 in these 10 years. Finally, you will have to add that number to the population amount to get the answer.
400,000 + 280,000 = 680,000
Class 2 scored better on average
<h3>How to determine which class scored better on average?</h3>
The averages and the standard deviations are given as:
Class 1
Mean score = 7.8
Standard deviation = 1
Class 2
Mean score = 8.1
Standard deviation = 0.2
As a general rule, the smaller the standard deviation; the better the average
Class 2 has a smaller deviation
Hence, class 2 scored better on average
Read more about standard deviation at:
brainly.com/question/28061243
#SPJ1
(f+g)(x) = f(x) + g(x) = (|x| + 9 ) + (-6) =
|x| + 9 - 6 = |x| + 3
Answer is |x| + 3